Hypohidrotic ectodermal dysplasia with autosomal inheritance: A rare entity - Ayushi Lodha; Shylaja Someshwar (Wolters Kluwer Medknow Publications, 2019)
Hypohidrotic ectodermal dysplasia (HED) is a rare disorder which is characterized by the involvement of all ectodermal derivatives and marked deficiency of sweating. It has a prevalence of 1: 100,000. X-linked recessive fashion is the most common pattern of inheritance, and 90% of the individuals affected are males. Autosomal dominant and recessive forms of this disease are very rare. Here, a 24-year-old female presented with classical features of HED: sparse lusterless hair, everted lips, and artificial dentures with a history of hypodontia in childhood. Patient's niece had complaints of decreased hair growth and sweating since birth. The patient also gave a history of similar complaints in great grandmother. Hence, we present an uncommon scenario where three females of an extended family were affected with HED and had symptoms of varying severity.